The Protection of Generator Stator Windings by Means of Subharmonic Current Method - Huseynov, E.N.; Abbasov, R.M.; Huseynov, F.H. (Herald of Azerbaijan Engineering Academy, 2023)
The article examines the subharmonic current method that protects the stator winding of the generator from ground faults. In the protection scheme based on the subharmonic current, the criteria of the subharmonic current angle ensure the high sensitivity of the relay protection. In modern microprocessor-based relay protection systems, more reliable and stable protection can be ensured by taking into account subharmonic currents.